(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Carsono N, Juwendah E, Liberty, Sari S, Damayanti F, Rachmadi M. 2021. Optimize 2,4-D concentration and callus induction time enhance callus proliferation and plant regeneration of three rice genotypes. Biodiversitas 22: 2555-2560. The development of callus in the course of transgenic rice avoids the somaclonal variants. To obtain a high number of normal phenotypes and a low number of somaclonal variants requires an appropriate 2,4-D concentration. In this study, we obtained the best callus induction time and a high number of green plant regeneration for three responsive rice genotypes on different 2,4-D concentrations in NB5 medium. The mature seeds of rice embryos were used as explants. A completely randomized factorial design was applied with four levels of 2,4-D concentrations (0, 1, 3, and 5 ppm), two levels of induction time (one and two weeks), and three rice genotypes (cv. Fatmawati, Nipponbare, and Kitaake). The study revealed that there was no interaction effect among genotype, 2,4-D concentration, and callus induction time. Three rice genotypes performed best in callus proliferation and regeneration. One-week callus induction time showed higher callus growth capacity (CGC) as compared to two-week callus induction time. Shoot regeneration capacity (SRC) was independently affected by genotype as well as by callus induction time. The interaction effect between 2,4-D concentration and callus induction time was observed on plant regeneration capacity (PRC). Without the addition of 2,4-D and 1 ppm of 2,4-D, the green plant regeneration capacity (GRC) was comparatively higher. Addition of 2,4-D showed a significant effect, especially at the plant regeneration stage. We found that one-week callus induction was the best treatment for callus proliferation and plant regeneration. We recommend the use of one-week callus induction and 1 ppm of 2,4-D for rice callus proliferation (sub-culture) and subsequent plant regeneration.